Law Enforcement During the Implementation of Large-Scale Social Restrictions in The Covid-19 Era: A Legal Perspective - Nurkhadijah, Hiksyani; Prawira Buana, Andika; Pelupessy, Palupessy (Golden Ratio of Law and Social Policy Review, 2023)
The purpose of the study was to analyze the effectiveness of the application of sanctions during the implementation of Large-Scale Social Restrictions in Makassar City and also to find out the factors that influence the application of sanctions during the implementation of large-scale social restrictions in the city of Makassar. this research uses empirical legal research methods, namely to analyze the law seen as patterned community behavior in the lives of people who always interact and relate in societal aspects. The results of this study indicate the effectiveness of the application of sanctions during the implementation of PSBB in the city of Makassar, this has several obstacles in the results to find violators during the implementation of PSBB in the city of Makassar where there are some people who are still indifferent to the application of health protocols and regulations set by the government regarding the application of large-scale social restrictions in the city of Makassar. Factors affecting the application of large-scale social restrictions in Makassar City such as the existence of people who do not comply with the application of health protocols enforced during large-scale social restrictions appealed to by the government and the task force on the road which results in an increase in the spread of Covid-19, and there are people who do not believe covid is a deadly disease so they do not comply with the regulations enforced during large-scale social restrictions appealed to by the government. Assertiveness in prosecuting an act that results in a violation either that does not comply with the implementation of health protocols or regulations that have been appealed to by the Makassar government on the implementation of large-scale social restrictions.